O Pronaf no Nordeste: Análise a partir dos dados do Censo Agropecuário de 2017 - César Nunes de Castro; Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The goal of the study is to analyze family farmers in Brazilian Northeast Region, based on a brief approach and the Pronaf insertion in that area. Exploratory analysis was developed based on 2017 agricultural census. Results highlight great number of agricultural units which raise animals or dedicated to some kind of farming, especially medium size animal, horticultural production and plant extractivism. There is notable family units and non-family units income disparity. In family units, agricultural activities from Pronaf farmers are the major income responsible, although income arising from non-agricultural activities cannot be denied. Other public policies deserve to be improved in that region, that is, infrastructure, rural extension, and agricultural insurance. There are several contingency factors especially relevant for local small and Pronaf producers, that is, the technological base and the guarantee assets asked for concluding the Pronaf loans. Moreover, local migratory process has diminished the number of young producers, a critical point for long-term Pronaf's impact and, fi nally yet importantly, the water disputes in Brazilian Northeast.
Keywords: Q10; Q18; 330; Brazil; Northeast region; agricultural; Pronaf; agricultural census